Genetic analysis and traits association in two double haploid populations of bread wheat (Triticum aestivum L.) - Singh, Gyanendra; Singh, Muneendra Kumar; Saharan, Mahender Singh; Singh, Charan; Tyagi, Bhuvdeva Singh; Sharma, Indu (Journal of Cereal Research, 2012)
A study was conducted for genetic analysis and estimating association of the traits in double haploid populations of bread wheat (Triticum aestivum L.). These populations were planted at Directorate of Wheat Research, Karnal during rabi season 2008-09 and 2009-10 in augmented design along with five checks in three blocks, wherein all checks were repeated in each block. The genetic variance and correlation coefficients were carried out for assessment of the performance of double haploid lines derived from the cross (Ducula4/2* Brookton) and (Camm/ HD 2329), through six metric traits, viz. plant height, days to heading, days to maturity, tillers per plot, 1000-grain weight and grain yield. Analysis of variance on the basis of F- values, revealed wide variability for most of the traits over the year and pooled. The phenotypic coefficient of variation (PCV) was higher than genotypic coefficient of variation (GCV) for all traits, while high heritability (<60%) coupled with high genetic advance (<15%) was found for all the traits, excepting the days to maturity and spike length. At phenotypic level, positive and significant correlation coefficients revealed that grain yield is directly influenced by spike length, tillers per plot and thousand grain weight, while significant and negative correlations was found of plant height and days to maturity with grain yield, respectively in both the populations. There is wide genetic diversity available for metric traits, which may be utilized for yield improvement in bread wheat through planned hybridization and selection. The traits plant height, maturity days, tillers per plot, spike length and 1000-grain weight of both populations can be of importance in further yield enhancement.